Barraquer‐Simons syndrome in systemic lupus erythematosus: A case report - Suman Acharya (Wiley, 2021)
Abstract Barraquer‐Simons syndrome is a rare entity characterized by progressive loss of subcutaneous tissue in the face and/or upper half of the body and can be associated with autoimmune conditions such as systemic lupus erythematosus. Close long‐term follow‐up is required to identify metabolic disturbances, potentially life‐threatening renal problems, and other associated diseases.